2006
DOI: 10.1002/bit.21064
|View full text |Cite
|
Sign up to set email alerts
|

Integrated non‐invasive system for quantifying secreted human therapeutic hIL2

Abstract: Cell encapsulation has been used to treat diabetes, amyotrophic lateral sclerosis, and other chronic ailments by the secretion of therapeutic proteins in vivo. Detection of these proteins typically requires invasive procedures such as blood sampling or device extraction, however. In this article, a non-invasive means of measuring secreted protein concentration using a co-expressed red fluorescent protein marker is developed. A bicistronic expression vector was constructed for the intracellular production of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Cultures transfected with pF3 rather than pF2 had slightly higher levels of red fluorescence at each overlay thickness, demonstrating the protective effects of Bcl‐2Δ 30–32. This finding is consistent with previous results, which showed that Bcl‐2Δ not only lessened necrosis and apoptosis but also augmented protein production in various mammalian cultures 25…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Cultures transfected with pF3 rather than pF2 had slightly higher levels of red fluorescence at each overlay thickness, demonstrating the protective effects of Bcl‐2Δ 30–32. This finding is consistent with previous results, which showed that Bcl‐2Δ not only lessened necrosis and apoptosis but also augmented protein production in various mammalian cultures 25…”
Section: Resultssupporting
confidence: 91%
“…The pF2 vector allowed constitutive secretion of hIL2 using a CMV promoter and tandem intracellular expression of DsExDR using an internal ribosome entry site (IRES). 25 The pF3 vector is the same as pF2 with the addition of an antiapoptotic gene, bcl-2D, placed downstream of a hypoxia inducible promoter, 5HRE-hCMVmp (5HRE). pF3 was constructed by modifying a previously constructed plasmid, pO2Ybp, which contains a 5HRE-EYFP-bcl-2D sequence.…”
Section: Vector Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…Signal transduction-expression of DsRed on per cell basis Plasmids pCT6 and pET200/DsRed (Yung et al, 2006;Tsao et al, 2010) were sequentially transformed into the E. coli W3110 luxS deletion mutant, W3110ΔluxS, and grown in LB media with appropriate antibiotics. Plasmid pCT6 senses and responds to the presence of phosphorylated AI-2 by the expression of T7 RNA polymerase, which, in turn, activates T7 polymerase-mediated overexpression of DsRed from plasmid pET200/DsRed.…”
Section: Resultsmentioning
confidence: 99%